Rural community-based organizations and cycle of harmful cultural practices against women and girls: Exploring gender-based violence and women liberation potentials (Research, Society and Development, 2026)
Harmful cultural practices against women and girls in the developing nations have some resilience against many eradication strategies by governmental and nongovernmental organizations. This challenge has been fluidlyconnected with unseen institutionalized structures and women institution in the rural communities.This article aims to present a study on rural community organizations and the cycle of harmful cultural practices against women and girls. This study was carried out in southeast Nigeria among rural women associations using quantitative and qualitative research methods. The study was guided by Anthony Giddens’ Structuration theory. The study involved 1098 respondents for questionnaire administration and 44 participants for Focused Group Discussion and In-Depth Interviews. Data were collected withpretested interviewer designed questionnaire developed from the elements of Social Norms and Beliefs About GBV Scaleand Quantitative measurement of gendered social normsas well as interview guide. The collected data were analysed using inferential statistics and thematic approach to the qualitative data. The study finds a negative correlation between engagement with community-based association and vulnerability to harmful cultural practices against women and girls in rural southeast Nigeria (rho = -.454, P. 000).Vulnerability to harmful cultural practices against women andgirls is predicted y education, age, average monthly income in Naira, residential, early marriage and family history of gender-based violence(R= 0.784 (61.5%), F= 62.791, P= .05).